Producción del documental: “la mendicidad en las calles de Guayaquil - León Chang, Karen (2010)
The purpose of the following documentary is to try to change the idea that people have about the mendicity by giving another perspective to the audience concerning this topic and in this way not to create wrong stereotypes about these human beings, whether the way the wear, their skin color, age or physique lacks. So it´s considered to put them aside from the society, reducing their self-esteem and transforming them vulnerable to any kind of injury whether physique or verbal, so they can be taken to other kinds of acts like drug addiction, rob or prostitution, therefore we want to show real testimonies and in this way the society can supply a solution and help together with some institutions and specialists like psychologists, social workers, and sociologists, so it can be eradicated this problematical. Besides we´ll provide the names of these organizations which work to rescue these people from the streets. The documentary is an element which will be used like a way to spread the message that we want to give, since it´s a visual proposal, it´ll be a bigger attraction to audience.